Формування лідерського потенціалу інтелігента - Гура, Тетяна Віталіївна; Пономарьов, Олександр Семенович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Обґрунтовано значення розвитку лідерських якостей представників різних верств інтелігенції як важливої передумови успішного виконання ними своєї суспільної місії. Показано, що належний лідерський потенціал у поєднанні з високою загальною і професійною культурою інтелігента та його багатим духовним світом істотно підвищує можливості і творчої діяльності інтелігента, і з його впливу на розвиток духовності й культури широких верств населення. Проаналізовано сенс понять “інтелігентність лідера” та “лідерство інтелігента”, розкрито їхню роль в процесах суспільного розвитку. Показано цілі, зміст і характер формування рис і якостей лідерства та інтелігентності майбутніх фахівців Розглянуто можливість використання синергетичного ефекту, що виникає в результаті цільового розвитку якостей інтелігентності та лідерства студентів як майбутніх фахівців під час формування їхньої професійної та соціальної компетентності.

The importance of the leadership qualities development of representatives of various strata of the intelligentsia as an important prerequisite for the successful implementation of their social mission is substantiated. It is shown that proper leadership potential in combination with high general and professional culture of an intellectual and his rich spiritual world significantly increases the opportunities and creative activity of an intellectual and his influence on the spirituality and culture of the general population. The meaning of the concepts of intelligence of a leader and leadership of an intellectual is analyzed, and their role in the processes of social development is revealed. The goals, content and nature of the formation of traits and qualities of leadership and intelligence of future professionals are revealed. The possibility of using the synergetic effect that arises as a result of targeted development of the qualities of intelligence and leadership of students as future professionals in the process of forming their professional and social competence is considered.
Formation of leadership potential of intellectual
Keywords: синергетичний ефект; лідер; інтелігент; лідерські якості; лідерський потенціал; загальна і професійна культура; суспільна місія; духовність; synergetic effect; social mission; leader; intellectual; leadership qualities; leadership potential; general and professional culture; spirituality